PERAN MEDIASI RENCANA BEROBAT DAN MODERASI KONTROL KEPERILAKUAN AKTUAL DAN KONTEKS SITUASIONAL DALAM HUBUNGAN ANTARA NIAT BEROBAT - Andika Anang Winarso; Waluyo Budi Atmoko; Finisha Mahaestri Noor (Jurnal Bisnis dan Kewirausahaan, 2020)
This study aims to examine the mediating role of the implementation plan in the relationship between medical intention and treatment decisions, examine the role of moderation of actual behavioral control in the relationship between implementation plans and treatment decisions, and examine the role of situational context moderation in the relationship between treatment plans and treatment decisions. The decision to treat a patient is important for the hospital because it determines the number of patients who will seek treatment at the hospital. Data obtained through questionnaires distributed to patient or someone who want to be a patient. The research sample used amounted 200. This research use purposive sampling in Solo Raya. Hypothesis testing used regression logistic for mediating and moderating role. First hypothesis are supported but second and third hypothesis was not supported.